Hybrid Beehive Innovation - De Jakes Olwendo, Kenya - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
50 smallholder farmers from East Africa showcased a number of interesting agricultural innovations at a farmer fair held in May 2013. De Jake Olwendo was one of the innovators under the livestock production category. He has combined aspects of the Kenya Top Bar Hive (KTBH) and the Langstroth beehive to come up with a cost effective hybrid beehive. The fair was co-organized by Promoting Local Innovation in ecologically oriented agriculture and natural resource management (PROLINOVVA) together with the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) and other partners. Stories from the innovations fair: http://ow.ly/mjE01